Analysis of Airborne Particulate Matter Concentrations During Rainstorms in Boston, Massachusetts. - Shapero, Andrew D. (Tufts Archival Research Center, 2014)
Abstract: Even though there is precipitation in Boston an average of 127 days out of the year, there have been few efforts to measure particulate air pollution during rainstorms in Boston. During rainstorms, particle number concentration (PNC), which is an air pollutant associated with cardiovascular disease, and meteorological conditions both change. It is unclear, however, if the rainfall itself or the changes in meteorological conditions cause PNC to change. The objectives of this study were: (1) to quantify the changes in PNC, temperature, atmospheric pressure, relative humidity, wind speed, and wind direction during rainstorms; (2) to construct a multivariate linear regression model to determine how PNC is associated with rainstorm duration; and (3) to determine which meteorological conditions are associated with changes in PNC during rainstorms. The study was performed at the Massachusetts Department of Environmental Protection (MassDEP) Air Pollution Monitoring Site in Roxbury, Massachusetts. PNC and meteorological conditions (temperature, atmospheric pressure, relative humidity, wind speed, wind direction, and rainfall rate) were measured at five-minute intervals from September 9, 2013 through March 12, 2014. A multivariate linear regression model and a time series of rainstorms were constructed. Average PNC during rainy weather was measured to be 8% less than average PNC during dry weather (p<0.001). In general, PNC levels decreased throughout rainstorms at a rate of 15%/hour. A multivariate linear regression model estimated that rainfall was associated with PNC removal at an average rate of 12%/hour. A comparison of the simple linear regression model and the multivariate linear regression model indicated that the decrease in PNC associated with rainfall duration is associated with the rainfall itself and not other meteorological conditions.